Efficiency of moderately hypofractionated radiotherapy in NSCLC cell model - Lüdeking, Marcus; Stemwedel, Katharina; Ramachandran, Dhanya; Grosche, Sinja; Christiansen, Hans; Merten, Roland; Henkenberens, Christoph; Bogdanova, Natalia V. (Frontiers in Oncology, 2024)
Background: The current standard of radiotherapy for inoperable locally advanced NSCLCs with single fraction doses of 2.0 Gy, results in poor outcomes. Several fractionation schedules have been explored that developed over the past decades to increasingly more hypofractionated treatments. Moderate hypofractionated radiotherapy, as an alternative treatment, has gained clinical importance due to shorter duration and higher patient convenience. However, clinical trials show controversial results, adding to the need for pre-clinical radiobiological studies of this schedule. Methods: We examined in comparative analysis the efficiency of moderate hypofractionation and normofractionation in four different NSCLC cell lines and fibroblasts using several molecular-biological approaches. Cells were daily irradiated with 24x2.75 Gy (moderate hypofractionation) or with 30x2 Gy (normofractionation), imitating the clinical situation. Proliferation and growth rate via direct counting of cell numbers, MTT assay and measurements of DNA-synthesizing cells (EdU assay), DNA repair efficiency via immunocytochemical staining of residual H2AX/53BP1 foci and cell surviving via clonogenic assay (CSA) were experimentally evaluated. Results: Overall, the four tumor cell lines and fibroblasts showed different sensitivity to both radiation regimes, indicating cell specificity of the effect. The absolute cell numbers and the CSA revealed significant differences between schedules (P < 0.0001 for all employed cell lines and both assays) with a stronger effect of moderate hypofractionation. Conclusion: Our results provide evidence for the similar effectiveness and toxicity of both regimes, with some favorable evidence towards a moderate hypofractionation. This indicates that increasing the dose per fraction may improve patient survival and therapy outcomes.